Microbiology of Ethiopian Traditionally Fermented Beverages and Condiments - Bikila Wedajo Lemi (International Journal of Microbiology)
Globally, fermented beverage and condiments are made by using different conventional practices, raw materials, and microorganisms. This paper presents the available literature review on the technology and microbiology of traditional Ethiopian beverages and condiment products. Traditional fermented beverage and condiment products have essential vitamins, minerals, enzymes, and antioxidants that are all enhanced through the process of traditional fermentation practices. In Ethiopia, fermented beverage and condiment products have practiced in a long history. During the production of traditional fermented beverage and condiment products, controlled natural fermentation process with the absence of starter cultures are used to initiate it. Moreover, the preparation of many traditionally fermented beverage and condiment products is still practiced in a household art, thereby a wide variety of fermented beverages and condiments are consumed in Ethiopia. In conclusion, the review discusses the nature of the beverage and condiment preparation, poor traditional household processing, and the extent and limitation of scientific work done so far and suggests some recommendations to limit the problem in Ethiopia.